Analysis of Ground and Surface Water Samples from some Area of Dhaka City for Polycyclic Aromatic Hydrocarbons (PAHs) - Mandal, S; Khuda, N; Mian, MR; Moniruzzaman, M; Nahar, N; Mamun, MIR; Shoeb, M (Dhaka University Journal of Science, 2015)
Abstract not available DOI: http://dx.doi.org/10.3329/dujs.v63i1.21770 Dhaka Univ. J. Sci. 63(1): 59-60, 2015 (January)